Financial Feasibility of Layers Farming Business - Ary Bakhtiar; Wahid Muhammad Shodiq; M. Zul Mazwan; Luinasia Elikunda Kombe (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2023)
Egg prices exhibit high volatility over short time intervals, which is notsurprising given their affordability and popularity as a primary proteinsource. However, this fluctuation in prices poses significantchallenges for businesses, particularly in managing cash flow. Hence,it becomes crucial to evaluate the feasibility and sensitivity of theLayers farming business at PT JIF. The objective of this research is toprovide a comprehensive analysis of the characteristics, financialaspects, cost flow, and overall feasibility of PT JIF's Layers farmingoperations. To achieve this, the study employs several data analysismethods, including the Net Present Value (NPV), Internal Rate ofReturn (IRR), Net B/C ratio, and Payback Period techniques. Thesemethods are used to assess the economic viability of PT JIF's Layersfarming business. The results demonstrate that PT JIF's layer farmingbusiness is indeed feasible, meeting the established investmentfeasibility criteria. Specifically, the NPV is greater than zero, the IRRexceeds the discount rate, the Net B/C ratio is higher than one, andthe payback period is within three years, which is shorter than thecommercial life of PT JIF's Layers farming business. For aspiringfarmers venturing into the layer farming industry, it is advised toexercise patience, resilience, and consistency, considering the returnon-investmentperiodofapproximatelythreeyears.Moreover,future researchersareencouragedtoconductsensitivityanalysestoexplore the potential effects of uncertainties on PT JIF's Layers farmingbusiness in the long term. By incorporating such sensitivity analyses,a more comprehensive understanding of the business's potentialperformance under varying circumstances can be obtained. This, inturn, would aid in making informed decisions and implementingeffective strategies for sustained success in the Layers farming sector